Carbonized steel slag auxiliary cementitious material, preparation method and application

CN123003242APending Publication Date: 2026-10-30ANSTEEL GROUP MINING CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202611380692.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0009]为解决现有技术中钢渣利用率低、体积稳定性差,以及传统CO2捕集提纯过程能耗高、常规CO2吸收-矿化一体化工艺存在固废传质受限及吸收液循环再生能力衰减,碳化后钢渣资源化利用率低等问题,本发明提供了一种基于CO2吸收和矿化一体化工艺制备碳化钢渣辅助性胶凝材料的方法,本发明公开的技术方案利用氨水、有机胺等为介质的CO2吸收矿化一体化工艺,通过CO2吸收介质强化钢渣碳酸化反应,突破烟气CO2流速与矿化速率不匹配问题;通过机械力活化与富碳吸收液离子环境协同作用,实现钢渣活性钙相持续释放、通过矿化实现CO2吸收剂解吸再生;通过CO2吸收介质对钢渣碳酸化产物晶型调控作用解决传统吸收剂高温再生能耗高的问题,实现碳化钢渣作为辅助性胶凝材料对水泥等胶凝材料力学性能的选择性提质,具有较好实用价值

Benefits of technology

(1)现有技术中,由于钢渣中含有游离氧化钙和游离氧化镁,易导致体积安定性不良,且其胶凝活性较低,使得钢渣的实际利用率仅为30%左右。本发明通过预先碳化改性工艺,将钢渣中的f-CaO、f-MgO转化为稳定的碳酸盐,彻底消除了膨胀隐患。同时,碳化过程生成的微纳米碳酸钙和高活性无定形SiO2,有效提升了材料的胶凝活性。实验数据表明,本发明制备的负碳全固废胶凝材料28d抗压强度可达30MPa,相较于未碳化体系提升了50%以上,突破了钢渣难以大量利用的技术瓶颈。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003242A_ABST
    Figure CN123003242A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of solid waste resource utilization, and specifically discloses a carbonized steel slag auxiliary cementing material, a preparation method and application, and comprises the following steps: steel slag pretreatment and mechanical activation-carbonization reaction-mineralization coupling-solid-liquid separation-preparation of the carbonized steel slag auxiliary cementing material; CO2-containing waste gas is introduced into an absorption tower to perform a carbonization reaction with a CO2 absorbent solution to form a CO2-rich solution, the CO2-rich solution is then injected into a desorption tower to perform a mineralization reaction with steel slag powder to generate a mixture slurry, solid-liquid separation is then performed to obtain carbonized steel slag, the carbonized steel slag is mixed with cementing material, curing is performed, and the carbonized steel slag auxiliary cementing material is obtained. The scheme can realize the regulation of the product by the CO2 absorbent, and thus the performance of the cementing material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solid waste resource utilization technology, specifically involving an auxiliary cementitious material for carbonized steel slag, its preparation method, and its application. Background Technology

[0002] my country's crude steel production accounts for more than half of the world's total, with an annual steel slag production of approximately 140 million tons, but the actual utilization rate is only about 30%. Steel slag also contains free calcium oxide (f-CaO) and magnesium oxide (f-MgO), leading to poor volume stability in engineering applications. Furthermore, my country's steel industry emits a large amount of CO2 waste gas during production, accounting for 15% of the country's total CO2 emissions. CO2 can neutralize free oxides in steel slag, promoting its application. On the one hand, purified CaCO3 has high economic value; on the other hand, carbonized steel slag mixtures can be used as auxiliary cementitious materials, improving the activity of cement and other cementitious materials. Steel slag carbonation is one of the effective measures for pollution reduction and carbon reduction in the steel industry (CN101851071A). However, most current steel slag carbonation technologies require CO2 capture and concentration, with CO2 capture costs accounting for about half, resulting in high overall process costs and hindering industrial application. However, CO2 mineralization does not require high CO2 concentrations. Ensuring efficient carbonation of steel slag while reducing CO2 capture costs is an urgent problem to be solved.

[0003] To address the high cost of steel slag carbonization processes, existing technologies typically employ direct mineralization using low-concentration CO2 waste gas. This reduces the overall cost by removing the CO2 capture process, specifically by utilizing a fluidized bed to achieve carbonation of steel slag powder under flue gas conditions (CN104759203B) and a carbonation chamber to achieve carbonation and curing of steel slag block materials under low-concentration CO2 flue gas conditions. However, direct mineralization using low-concentration CO2 waste gas presents the following problems: (1) the flue gas emission rate is fast, resulting in a low reaction rate for low-concentration CO2 mineralization and thus a low CO2 conversion rate; (2) the flue gas contains impurities such as SO2, CO, and NO. x These factors have a negative impact on the carbonation of steel slag.

[0004] To address the mismatch between flue gas emission velocity and CO2 mineralization rate, most methods employ reducing flue gas velocity and increasing the CO2 mineralization rate. Regarding the slow carbonation reaction of steel slag, it is typically improved through mechanical activation and chemical activation (CN103111186B, CN115626788B, CN117185334A). While mechanical activation has a simple process, grinding consumes a lot of energy. Chemical activation suffers from high costs of chemical additives, and the difficulty in recovering chemical reagents poses potential environmental problems.

[0005] Regarding the impact of impurities in flue gas, studies have found that small amounts of SO2 can promote the carbonation of steel slag. However, direct utilization of CO-containing flue gas may lead to CO leakage and environmental pollution. To avoid the impact of impurities, multi-stage removal of flue gas impurities or CO2 capture is required, resulting in high costs. Among CO2 capture methods, the most common method is CO2 absorption, which regenerates the absorbent by raising the temperature. The heating and cooling process accounts for 90% of the total energy consumption. Therefore, integrating CO2 absorption and mineralization, utilizing CO2 mineralization of steel slag to regenerate the absorbent and eliminating the heating and cooling process, holds promise for achieving low-concentration, low-cost, and efficient CO2 mineralization.

[0006] CN108246090A discloses a wet decarbonization process using steel slag slurry. This method utilizes waste steelmaking slag as an absorbent to absorb carbon dioxide. The waste steelmaking slag is ground and mixed with water to form a slurry. Flue gas is then passed through the slurry to achieve decarbonization. The decarbonized slurry produces a precipitate primarily composed of calcium carbonate. The entire decarbonization process recycles waste materials such as steel slag, saving on absorbent costs compared to traditional decarbonization processes and achieving efficient removal of carbon dioxide from flue gas. However, this process does not employ a CO2 absorbent to pre-capture CO2. Because the absorption medium is a steel slag-water slurry, the carbonation rate of the steel slag is much lower than the CO2 flow rate in the flue gas, resulting in a low CO2 capture rate.

[0007] CN118371110A discloses a method and system for integrated carbon dioxide absorption and mineralization regeneration coupled backfilling. This scheme reacts the CO2-rich liquid obtained by organic amine absorbent with calcium and magnesium ions to achieve low-energy regeneration and reuse of organic amine absorbent, improve the reaction rate of CO2 mineralization, and achieve the triple goals of low-energy emission reduction of carbon dioxide, resource utilization of solid waste and backfilling in coal mines. However, this scheme cannot achieve the regulation of products through CO2 absorbent and is difficult to improve the performance of cementitious materials.

[0008] In summary, existing technologies have largely failed to simultaneously address the technical challenges of slow direct mineralization reaction rates of low-concentration CO2 in flue gas, mismatch between CO2 flow rate and mineralization rate, and high energy consumption for high-temperature regeneration of traditional absorbents. Consequently, they cannot achieve the regulation of the crystal form of carbonation products of steel slag by the CO2 absorption medium, and thus cannot fully leverage the selective quality-enhancing effect of carbonized steel slag as an auxiliary cementing material on the mechanical properties of cement and other cementitious materials. Summary of the Invention

[0009] To address the problems of low utilization rate and poor volume stability of steel slag in existing technologies, as well as the high energy consumption of traditional CO2 capture and purification processes, limited solid waste mass transfer and reduced regeneration capacity of absorbent liquid in conventional integrated CO2 absorption-mineralization processes, and low resource utilization rate of carbonized steel slag, this invention provides a method for preparing auxiliary cementitious materials from carbonized steel slag based on an integrated CO2 absorption and mineralization process. The disclosed technical solution utilizes an integrated CO2 absorption and mineralization process with ammonia and organic amines as media. This process enhances the carbonation reaction of steel slag through the CO2 absorption medium, overcoming the mismatch between flue gas CO2 flow rate and mineralization rate. Through the synergistic effect of mechanical activation and the carbon-rich absorbent ion environment, the continuous release of active calcium phase from the steel slag is achieved, and the CO2 absorbent is desorbed and regenerated through mineralization. The CO2 absorption medium's effect on the crystal form regulation of the carbonation products of the steel slag solves the problem of high energy consumption in the high-temperature regeneration of traditional absorbents. This allows carbonized steel slag to selectively improve the mechanical properties of cement and other cementitious materials as an auxiliary cementitious material, demonstrating significant practical value.

[0010] The objectives of this invention include: 1. Overcome the mass transfer barrier during the mid-stage gel passivation period, thereby increasing the degree of carbonation and reaction rate of steel slag. Existing technologies often encounter problems when treating complex silicate solid wastes such as steel slag. The formation of dense films on particle surfaces by early-stage CSH gels and monocarbonates hinders the coupling and diffusion of CO2 and calcium ions, leading to reaction stagnation (i.e., passivation). This invention couples mechanical activation with the mineralization process, avoiding reliance on conventional short-term static pretreatment. Instead, it dynamically controls the intensification of lattice defects and continuously peels off the surface passivation layer, resulting in secondary exposure of the internal active calcium phase. This breaks down the mass transfer barrier during the mid-stage gel passivation period, improving the carbonation degree and reaction kinetics rate of the steel slag.

[0011] 2. Overcomes the high viscosity and slow CO2 molecule diffusion of single organic ammonia, ensuring cycle load and regeneration efficiency. The existing technologies for directly adding calcium sources to single organic sterically hindered amine systems (such as AMP or MDEA) face challenges such as low solubility, limited mass transfer, and intermediate products (such as NH2COO) during the recycling process of single ammonia systems. - The problem of incomplete desorption leading to a decline in the circulation capacity of the absorbent is addressed by optimizing the composite absorbent system (introducing a specific concentration of ammonium ions or using an ammonia / organic amine composite system). This system overcomes the shortcomings of high viscosity and slow CO2 molecule diffusion of single organic amine, and utilizes a specific ionic environment to greatly promote the rapid leaching of active calcium ions and rapid precipitation of calcium carbonate in steel slag, ensuring excellent circulation load and regeneration efficiency.

[0012] 3. Eliminates the enormous energy consumption of thermal regeneration and removes the potential for volume expansion caused by free calcium oxide and magnesium oxide. The technical solution disclosed in this invention deeply integrates CO2 capture, heatless chemical regeneration of absorbent, and stabilization modification of steel slag. Compared with the traditional absorbent regeneration process that relies on temperature-varying washing, this process eliminates the enormous energy consumption of thermal regeneration. Compared with conventional direct wet carbonization technology, the carbonized steel slag prepared by this invention not only completely eliminates the risk of volume expansion caused by free calcium oxide (f-CaO) and free magnesium oxide (f-MgO), but also the generated calcium carbonate can effectively fill and improve the mechanical properties of cement and other cementitious materials.

[0013] 4. Construct an auxiliary cementitious system based on carbide steel slag to break through the dependence of traditional cementitious materials on expensive admixtures. Most existing cementitious systems still require the addition of some cement clinker or rely on strong alkaline solutions (such as sodium hydroxide solution) to provide an initial alkaline environment to activate activity, failing to achieve true low carbon and low cost. This invention replaces part of the cementitious materials with carbide steel slag to construct a multi-component synergistic system. In this system, the highly active amorphous SiO2 in the carbide steel slag generates CS(A)-H gel under Ca-containing, highly alkaline conditions. Simultaneously, the CaCO3 generated in the carbide steel slag not only acts as a micro-aggregate filler but also reacts with complex salts such as ettringite to generate monocarbonate aluminates (Mc), thereby optimizing the microstructure. That is, by adjusting the carbonate crystal form in the carbide steel slag through a CO2 absorbent, the carbide steel slag is used as an auxiliary cementitious material to directionally enhance material performance.

[0014] According to a first aspect of the present invention, a carbide slag auxiliary cementitious material is provided, the carbide slag auxiliary cementitious material being composed of carbide slag and cementitious material; The carbide steel slag exhibits a mixed morphology of multiple mineral phases, with a carbon fixation content of 10-32%. The cementing material is a hydraulic inorganic cementing material; The mass ratio of the carbide steel slag to the cementitious material is 10~30:70~90, and the water-cement ratio is 0.25~0.6.

[0015] Based on the above technical solution, the cementitious material is selected from at least one of silicate cement, aluminate cement, sulfoaluminate cement, and solid waste-based cementitious material, preferably solid waste-based cementitious material, which is composed of steel slag, blast furnace slag, and desulfurized gypsum in a mass ratio of 2~6:3~7:0.5~2. The carbon fixation content of a unit cementitious material is 2-16%.

[0016] According to a second aspect of the present invention, a method for preparing a carbide slag-assisted cementitious material is provided, comprising the following steps: Step 1: Steel slag pretreatment and mechanical activation; Step 2, CO2 absorption reaction: CO2-containing waste gas is introduced into the absorption tower and reacts with the CO2 absorbent solution to form a CO2-rich solution. Step 3, mineralization coupling: The CO2-rich solution is injected into the stripping tower to react with the steel slag powder to generate a mixed slurry; Step 4: Solid-liquid separation: The mixed slurry is subjected to solid-liquid separation. The separated liquid phase is recycled back to the absorption tower as regeneration absorbent. The separated solid precipitate is dried to obtain carbide steel slag. Step 5: Preparation of auxiliary cementitious material for steel carbide slag: Mix steel carbide slag and cementitious material at a mass ratio of 10~30:70~90, with a water-cement ratio of 0.25~0.6, to obtain auxiliary cementitious material for steel carbide slag.

[0017] Based on the above technical solution, the steel slag pretreatment and mechanical activation are specifically as follows: the steel slag is dried at 60~100℃ to constant weight, sieved to obtain steel slag primary material with a particle size ≤7mm, and then ground to obtain steel slag micro powder. The steel slag is selected from at least one of converter steel slag, electric furnace steel slag, refining slag, hot metal pre-desulfurization slag, and foundry residue slag, and the CaO content in the steel slag is >20% by mass. The steel slag powder has a d50 particle size of 5~36.0μm and a specific surface area of ​​460~700m². 2 / kg; The grinding process specifically involves placing the initial steel slag material in a grinding equipment and continuously grinding it at a speed of 300~1500 rpm for 30~120 minutes, with a ball-to-material mass ratio of 9~25:1.

[0018] Based on the above technical solution, the CO2 absorbent solution is prepared by mixing CO2 absorbent and water in a mass ratio of 8~50:50~92, with a mass concentration of 8%~50%. The CO2 absorbent is an aqueous ammonia solution or an organic amine solution, wherein the organic amine solution is selected from at least one of aqueous solutions of ethanolamine (MEA), piperazine (PZ), 2-amino-2-methyl-1-propanol (AMP), and N-methyldiethanolamine (MDEA).

[0019] Based on the above technical solution, the CO2 absorption reaction is specifically as follows: at 20~60℃, CO2-containing waste gas is introduced at a flow rate of 10~100Nm / h until the pH of the CO2 absorbent solution is 8.5~9.5, to obtain a CO2-rich solution; the CO2 concentration in the CO2-containing waste gas is 2~60%, and it originates from steel plants, power plants, cement plants, and electrolytic aluminum plants.

[0020] Based on the above technical solution, the CO2-rich solution has a capture rate of 15-98% and a carbon fixation capacity of 20-80 g / L.

[0021] Based on the above technical solution, the mineralization reaction is specifically as follows: the mass ratio of steel slag powder to CO2-rich solution is 10%~50%, the CO2-rich solution is injected into the desorption tower at a flow rate of 60~480L / h, and the reaction is carried out at 20~60℃ with a stirring rate of 300~1600rpm for 10~60min. The desorption time for CO2-rich solutions is 10–60 min, with a maximum desorption rate of 60%–95%.

[0022] Based on the above technical solution, the solid-liquid separation is specifically as follows: separation is carried out by gravity sedimentation, sedimentation in a sedimentation tank for 15-60 minutes, solid particles are recovered, and the recovered solid particles are used for the preparation of carbide steel slag; the supernatant is refluxed.

[0023] Based on the above technical solution, the free calcium oxide (f-CaO) and free magnesium oxide (f-MgO) inside the carbide steel slag are converted into carbonates, and the products include calcium carbonate, magnesium carbonate, and nano-sized silica. Under different negative carbon absorption liquid conditions, the generated calcium carbonate and magnesium carbonate have different crystal forms. The calcium carbonate crystal forms include: aragonite, aragonite, calcite, and nano-calcium carbonate; the magnesium carbonate crystal forms include: magnesite, trihydrated magnesite, spheroidal magnesite, and hydromagnesite. The carbide steel slag has a mixed morphology of multiple mineral phases and a carbon fixation content of 10-32%.

[0024] Based on the above technical solution, the cementing material is a hydraulic inorganic cementing material, selected from at least one of silicate cement, aluminate cement, sulfoaluminate cement, and solid waste-based cementing materials, preferably a solid waste-based cementing material. The carbon sequestration of a unit cementing material is 22~160g CO2 / kg. The solid waste-based cementing material is composed of steel slag, blast furnace slag, and desulfurized gypsum in a mass ratio of 2~6:3~7:0.5~2.

[0025] According to a third aspect of the present invention, an application of a carbide slag auxiliary cementitious material is provided, wherein the carbide slag auxiliary cementitious material is made into a paste sample block, cured, and a hardened body is obtained.

[0026] Based on the above technical solution, the curing process specifically involves curing at 20~60℃ for 1~28 days under normal pressure.

[0027] Based on the above technical solution, the 3-day compressive strength of the hardened body is 0.7~8MPa, the 7-day compressive strength of the hardened body is 6~25MPa, and the 28-day compressive strength of the hardened body is 15~60MPa.

[0028] Beneficial effects (1) In the prior art, due to the presence of free calcium oxide and free magnesium oxide in steel slag, poor volume stability and low cementitious activity are easily caused, resulting in an actual utilization rate of only about 30%. This invention uses a pre-carbonization modification process to convert f-CaO and f-MgO in steel slag into stable carbonates, completely eliminating the risk of expansion. At the same time, the micro-nano calcium carbonate and highly active amorphous SiO2 generated during the carbonization process effectively improve the cementitious activity of the material. Experimental data show that the negative carbon all-solid waste cementitious material prepared by this invention can achieve a 28-day compressive strength of 30 MPa, which is more than 50% higher than that of the uncarbonized system, breaking through the technical bottleneck of the difficulty in large-scale utilization of steel slag.

[0029] (2) The technical solution disclosed in this invention organically combines CO2 mineralization and sequestration with solid waste resource utilization. By optimizing the carbonization process, the average carbon sequestration amount per unit of cementitious material can reach 40g CO2 / kg. Compared with direct stockpiling or utilization of low-value-added building materials, this invention achieves CO2 mineral sequestration while disposing of large quantities of industrial solid waste, providing a practical and feasible technical path for the steel industry to "reduce carbon and increase carbon sequestration", and has significant environmental benefits.

[0030] (3) The technical solution disclosed in this invention places the key carbonization and activation steps in advance, and the product is stable carbonized steel slag powder, which is easy to store and transport. Compared with the complex CO2 stirring and filling process or the subsequent carbonization and curing process of the filling body, the preparation of the subsequent filling material only requires a conventional mixing process. There is no need to carry out complex chemical reaction control or add special chemical reagents underground. The process is simple and easy to promote and implement in the existing mine filling system. It has both technical advancement and engineering applicability.

[0031] (4) The technical solution disclosed in this invention uses mechanical activation for a specific duration coupled with CO2 absorption liquid phase. Mechanical activation increases the porosity and lattice defects of steel slag, while also increasing the probability of secondary exposure of internal active calcium phase. Through this balance between physical wall breaking and specific liquid phase ion environment, the mass transfer barrier of CSH gel and monocarbonate dense film generated on the surface of steel slag is broken, preventing the carbonation reaction from being restricted due to the passivation layer encapsulating particles, thereby improving the carbonation conversion rate and reaction kinetic rate of steel slag. In addition, under the combined action of specific ions in carbon-rich absorption liquid and medium and low temperature, the intermediate complexes inside the absorption liquid system will accelerate reverse dissociation and couple with the freed calcium ions, further reducing the huge heat energy consumption of traditional variable temperature desorption, and improving the efficiency and cycle life of heatless in-situ chemical regeneration of absorption liquid.

[0032] (5) The technical solution disclosed in this invention, under the synergistic effect of deep mechanical activation, optimization of the ion environment of the absorbent liquid, and in-situ mineralization precipitation, can optimize the mechanical properties and stability of the carbonized steel slag product while ensuring that the absorbent liquid has good CO2 capture and cyclic desorption capabilities. Carbonization completely consumes free calcium oxide and magnesium oxide to eliminate the risk of volume expansion, and the calcium carbonate microcrystals generated in situ can effectively fill the micropores of cementitious materials or filling slurries, accelerate the densification of the cross-linked network of hydration products, and thus optimize the macroscopic compressive strength of low-carbon building materials or green mine filling materials. Attached Figure Description

[0033] Figure 1 A flow chart of the process for preparing carbide steel slag based on integrated CO2 absorption and mineralization; Figure 2 The TG-DTG diagrams for carbide steel slag are shown below (CSH: hydrated calcium silicate gel, carbide steel slag-ammonia water: Example 1, carbide steel slag-AMP: Example 2). Figure 3 SEM images of carbide steel slag in different CO2 absorbent media (a. Example 1, b. Example 2). Detailed Implementation

[0034] To make the objectives and technical solutions of this invention clearer, the following embodiments are provided for further explanation. However, the scope of protection of this invention is not limited to these embodiments; the embodiments are merely for illustrative purposes. Those skilled in the art should understand that any changes or equivalent substitutions that do not depart from the concept of this invention are included within the scope of protection of this invention.

[0035] Unless otherwise specified, all reagents and raw materials used in this invention are obtained through purchase.

[0036] Example 1: according to Figure 1 The process flow shown is used to prepare carbide steel slag; Step 1: Steel slag pretreatment and mechanical activation: 100 kg of converter steel slag was dried at 60℃ to constant weight and sieved to obtain initial steel slag material with a particle size ≤ 7 mm. Then, it was milled for 90 minutes at a ball-to-powder mass ratio of 9:1 to obtain activated steel slag micro powder with a d50 particle size reduced to 10.3 μm and a specific surface area of ​​496 m². 2 / kg.

[0037] Step 2, CO2 absorption reaction: with a flow rate of 10 Nm³ / h 3 Ammonia gas is passed through 100 kg of water at a concentration of 9% to obtain 110 kg of ammonia water. In an absorption tower, 60 kg of the ammonia water is used to capture CO2 (20% CO2 concentration) from steel plant flue gas. The gas-liquid absorption reaction is carried out at 40℃ for 30 min, with a concentration of 10 Nm³.3 The above-mentioned CO2-containing flue gas was introduced at a flow rate of / h until the pH value of the absorbent stabilized at 9.5, resulting in an ammonium carbonate solution. At this point, the CO2 capture rate was 74.9%, and the carbon fixation capacity of the ammonium carbonate solution was 76.1 g / L.

[0038] Step 3, mineralization coupling: The ammonium carbonate solution absorbent is injected into the desorption tower at a flow rate of 120 L / h. 6 kg of activated steel slag powder is added to 60 kg of ammonium carbonate solution at a solid-liquid ratio of 1:10 to carry out the mineralization coupling reaction. The reaction temperature is 40℃ at a stirring rate of 1500 rpm for 30 min. Calcium ions in the activated steel slag powder are leached out and combine with carbonate or bicarbonate ions in the liquid phase to form 7 kg of carbonate precipitate. At the same time, ammonium carbonate is desorbed (reaching the desorption peak in 10 min, with a maximum desorption rate of 92.50%), realizing the regeneration of ammonia water and obtaining a mixed slurry. Step 4, Solid-Liquid Separation: The mixed slurry undergoes solid-liquid separation using gravity sedimentation for primary separation. The mixture settles in a sedimentation tank for 30 minutes. The separated liquid phase is recycled back to Step 2 as regenerated ammonia water. The separated solid precipitate is dried at 60℃ for 24 hours to obtain carbide steel slag. The carbon content of the carbide steel slag is 16.63%. The carbide steel slag contains aragonite, spheroidal aragonite, and nano-silica. The TG-DTG and SEM test results of the carbide steel slag are shown below. Figure 2 , Figure 3 ; Step 5: Preparation of auxiliary cementitious material for carbide steel slag: 20 kg of carbide steel slag and 80 kg of solid waste-based cementitious material (steel slag: slag: desulfurized gypsum mass ratio of 6:3:1, carbon sequestration per unit cementitious material of 32.6 g CO2 / kg) were mixed at a mass ratio of 1:4 to form auxiliary cementitious material for carbide steel slag, with a water-cement ratio of 0.32. The auxiliary cementitious material was then prepared into neat cement paste test blocks. The curing conditions were 20℃ and atmospheric pressure. The compressive strength was tested after 3, 7, and 28 days of curing. The test results are shown in Table 1.

[0039] Example 2: according to Figure 1 The process flow shown is used to prepare carbide steel slag; Step 1: Steel slag pretreatment and mechanical activation: 100 kg of converter steel slag was dried to constant weight and sieved to obtain initial steel slag material with a particle size ≤ 7 mm. This material was then ground for 75 minutes at a ball-to-powder mass ratio of 9:1, resulting in activated steel slag micro-powder with a d50 particle size reduced to 9.5 μm and a specific surface area of ​​531.9 m². 2 / kg.

[0040] Step 2, CO2 Absorption Reaction: 36.5g of AMP (2-amino-2-methyl-propanol) and 100kg of water were mixed to prepare an AMP solution with a mass concentration of 26.79%. 60kg of CO2-rich AMP solution was used to capture CO2 from the power plant flue gas (CO2 concentration of 23%), and a gas-liquid absorption reaction was carried out at a reaction temperature of 40℃ and a flow rate of 10Nm³. 3 The CO2-containing flue gas was introduced at a flow rate of / h until the pH of the absorbent stabilized at 8.1, resulting in a CO2-rich AMP solution. At this point, the CO2 capture rate was 95.4%, and the carbon fixation capacity of the CO2-rich AMP solution was 112.4 g / L.

[0041] Step 3, Mineralization Coupling: A CO2-rich AMP solution is injected into the desorption tower at a flow rate of 240 L / h. 9 kg of activated steel slag powder is added to 60 kg of ammonium carbonate solution at a solid-liquid ratio of 3:20 to carry out a mineralization coupling reaction. The reaction is carried out at 40°C with a stirring rate of 1500 rpm for 15 min. Calcium ions in the activated steel slag powder are leached out and combine with carbonate or bicarbonate ions in the liquid phase to form carbonate precipitates. At the same time, the CO2-rich AMP solution is desorbed (the desorption peak is reached in 15 min, with a maximum resolution rate of 86.22%), thus regenerating the AMP solution and obtaining a mixed slurry. Step 4, Solid-Liquid Separation: The mixed slurry is subjected to solid-liquid separation using gravity sedimentation. The mixture is allowed to settle in a sedimentation tank for 30 minutes. The separated liquid phase is recycled back to Step 2 as the regenerated AMP solution. The separated solid precipitate is dried at 60℃ for 24 hours to obtain carbide steel slag. The carbon content of the carbide steel slag is 30.7%. Aragonite and nano-silica are formed inside the carbide steel slag. The TG-DTG and SEM test results are shown below. Figure 2 , Figure 3 ; Step 5: Preparation of auxiliary cementitious material for carbide steel slag: 20 kg of carbide steel slag and 80 kg of solid waste-based cementitious material (the mass ratio of steel slag: blast furnace slag: desulfurized gypsum is 6:3:1, and the carbon sequestration per unit cementitious material is 61.4 g CO2 / kg) are mixed at a mass ratio of 1:4 to form auxiliary cementitious material for carbide steel slag, with a water-cement ratio of 0.32. The auxiliary cementitious material is then prepared into neat cement paste test blocks. The curing conditions are a temperature of 20℃ and a pressure of normal atmospheric pressure. The compressive strength is tested after 3, 7, and 28 days of curing. The test results are shown in Table 1.

[0042] Example 3 according to Figure 1 The process flow shown is used to prepare carbide steel slag; Step 1: Steel slag pretreatment and mechanical activation: 100 kg of converter steel slag was dried to constant weight at 60℃ and sieved to obtain initial steel slag material with a particle size ≤7 mm. Then, it was ground for 120 minutes at a ball-to-powder mass ratio of 15:1 to obtain activated steel slag micro powder with a d50 particle size reduced to 8.3 μm and a specific surface area of ​​653 m². 2 / kg.

[0043] Step 2, CO2 Absorption Reaction: 50g of N-methyldiethanolamine (MDEA) and 50kg of water are mixed to form a 50% (w / w) MDEA solution. 60kg of this MDEA solution is used to capture CO2 from power plant flue gas (CO2 concentration 27%) in a gas-liquid absorption reaction at 40℃, with a flow rate of 10Nm³ / min. 3 The CO2-containing flue gas is introduced at a flow rate of / h until the pH of the absorbent stabilizes at 9.2, resulting in a CO2-rich MDEA solution. At this point, the CO2 capture rate is 28%, and the carbon fixation capacity of the CO2-rich MDEA solution is 30 g / L.

[0044] Step 3, mineralization coupling: The CO2-rich MDEA solution is injected into the desorption tower at a flow rate of 249 L / h. 12 kg of activated steel slag powder is added to 60 kg of CO2-rich MDEA solution at a solid-liquid ratio of 1:5 to carry out the mineralization coupling reaction. The reaction is carried out at 40℃ with a stirring rate of 1200 rpm for 30 min. Calcium ions in the activated steel slag powder are leached out and combine with carbonate or bicarbonate ions in the liquid phase to form carbonate precipitates. At the same time, the CO2-rich MDEA solution is desorbed (the desorption peak is reached in 10 min, with a maximum resolution rate of 70.58%), realizing the regeneration of the MDEA solution and obtaining a mixed slurry. Step 4, Solid-Liquid Separation: The mixed slurry is subjected to solid-liquid separation using gravity sedimentation. The mixture is settled in a sedimentation tank for 30 minutes. The separated liquid phase is recycled back to Step 2 as regenerated ammonia water. The separated solid precipitate is dried at 60°C for 24 hours to obtain carbide steel slag. The carbon content of the carbide steel slag is 11.2%, and aragonite, spheroidal aragonite, and nano-silica are generated inside the carbide steel slag.

[0045] Step 5: Preparation of auxiliary cementitious material for carbide steel slag: 20 kg of carbide steel slag and 80 kg of solid waste-based cementitious material (steel slag: blast furnace slag: desulfurized gypsum mass ratio of 6:3:1, carbon sequestration per unit cementitious material of 22.4 g CO2 / kg) were mixed at a mass ratio of 1:4 to form auxiliary cementitious material for carbide steel slag, with a water-cement ratio of 0.32. The auxiliary cementitious material was then prepared into neat cement paste test blocks. The curing conditions were 20℃ and atmospheric pressure. The compressive strength was tested after 3, 7, and 28 days of curing. The test results are shown in Table 1.

[0046] Comparative example: 50 kg of solid waste-based cementitious material (steel slag: blast furnace slag: desulfurized gypsum in a mass ratio of 6:3:1) was mixed with 16 kg of water at a water-cement ratio of 0.32 to prepare neat cement paste test blocks. The curing conditions were 20℃ and atmospheric pressure. The compressive strength was tested after 3, 7, and 28 days of curing, and the test results are shown in Table 1.

[0047] Table 1. Preparation conditions of carbide steel slag and its performance indicators as an auxiliary cementitious material

[0048] The results show that the compressive strength of Example 1 after 3 days and 7 days of curing is higher than that of the comparative example; the compressive strength of Example 2 after 28 days of curing is higher than that of the comparative example; and the compressive strength of Example 3 after 3 days, 7 days, and 28 days of curing is higher than that of the comparative example. The carbide steel slag auxiliary cementitious material prepared by the technical solution disclosed in this invention can increase the carbon fixation amount through a CO2 absorbent, regulate the carbonate crystal form, and directionally improve the early performance or long-term durability of the cementitious material.

[0049] Furthermore, the carbide steel slag auxiliary cementitious material prepared by the technical solution disclosed in this invention can replace part of the cementitious material, improve the performance of the cementitious material, and, based on its mechanical properties, be widely used in underground filling, soft soil stabilization, and other engineering projects. The technical solution disclosed in this invention can achieve low-cost and high-efficiency preparation of carbide steel slag auxiliary cementitious material, increasing the carbon fixation capacity of the material while improving its mechanical properties.

[0050] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. An auxiliary cementitious material for carbide steel slag, characterized in that, The auxiliary cementitious material for carbide steel slag is composed of carbide steel slag and cementitious materials; The carbide steel slag exhibits a mixed morphology of multiple mineral phases, with a carbon fixation content of 10-32%. The cementing material is a hydraulic inorganic cementing material; The mass ratio of the carbide steel slag to the cementitious material is 10~30:70~90, and the water-cement ratio is 0.25~0.

6.

2. The auxiliary cementitious material for carbide steel slag according to claim 1, characterized in that, The cementitious material is selected from at least one of silicate cement, aluminate cement, sulfoaluminate cement, and solid waste-based cementitious material, preferably solid waste-based cementitious material, which is composed of steel slag, blast furnace slag, and desulfurized gypsum in a mass ratio of 2~6:3~7:0.5~2. The carbon fixation content of a unit cementitious material is 2-16%.

3. The method for preparing the auxiliary cementitious material of carbide steel slag according to any one of claims 1 or 2, characterized in that, Includes the following steps: Step 1: Steel slag pretreatment and mechanical activation; Step 2, CO2 absorption reaction: CO2-containing waste gas is introduced into the absorption tower and reacts with the CO2 absorbent solution to form a CO2-rich solution. Step 3, mineralization coupling: Inject the CO2-rich solution into the stripping tower to react with the steel slag powder to generate a mixed slurry; Step 4: Solid-liquid separation: The mixed slurry is subjected to solid-liquid separation. The separated liquid phase is recycled back to the absorption tower as regeneration absorbent. The separated solid precipitate is dried to obtain carbide steel slag. Step 5: Preparation of auxiliary cementitious material for steel carbide slag: Mix steel carbide slag and cementitious material at a mass ratio of 10~30:70~90, with a water-cement ratio of 0.25~0.6, to obtain auxiliary cementitious material for steel carbide slag.

4. The preparation method according to claim 3, characterized in that, The steel slag pretreatment and mechanical activation are specifically as follows: the steel slag is dried at 60~100℃ to constant weight, sieved to obtain steel slag primary material with a particle size ≤7mm, and then ground to obtain steel slag micro powder. The steel slag is selected from at least one of converter steel slag, electric furnace steel slag, refining slag, hot metal pre-desulfurization slag, and casting residue slag, and the CaO content in the steel slag is >20% by mass. The steel slag powder has a d50 particle size of 5~36.0μm and a specific surface area of ​​460~700m². 2 / kg; The grinding process specifically involves placing the initial steel slag material in a grinding equipment and continuously grinding it at a speed of 300~1500 rpm for 30~120 minutes, with a ball-to-material mass ratio of 9~25:

1.

5. The preparation method according to claim 3, characterized in that, The CO2 absorbent solution is prepared by mixing CO2 absorbent and water in a mass ratio of 8~50:50~92, with a mass concentration of 8%~50%. The CO2 absorbent is an aqueous ammonia solution or an organic amine solution, wherein the organic amine solution is selected from at least one of ethanolamine, piperazine, 2-amino-2-methyl-1-propanol, and N-methyldiethanolamine aqueous solution; The CO2 absorption reaction specifically involves: passing CO2-containing waste gas through the gas at a flow rate of 10-100 Nm / h at 20-60°C until the pH of the CO2 absorbent solution reaches 8.5-9.5, thereby obtaining a CO2-rich solution; the CO2 concentration in the CO2-containing waste gas is 2-60%, originating from steel plants, power plants, cement plants, and electrolytic aluminum plants; The CO2-rich solution has a capture rate of 15-98% and a carbon fixation capacity of 20-80 g / L.

6. The preparation method according to claim 3, characterized in that, The mineralization reaction is specifically as follows: the mass ratio of steel slag powder to CO2-rich solution is 10%~50%, the CO2-rich solution is injected into the desorption tower at a flow rate of 60~480L / h, and the reaction is carried out at 20~60℃ with a stirring rate of 300~1600rpm for 10~60min. The desorption time for CO2-rich solutions is 10–60 min, with a maximum desorption rate of 60%–95%.

7. The preparation method according to claim 3, characterized in that, The solid-liquid separation is specifically carried out by gravity sedimentation, with sedimentation in a sedimentation tank for 15-60 minutes, recovery of solid particles, and use of the recovered solid particles for the preparation of carbide steel slag, while the supernatant is recycled.

8. The preparation method according to claim 3, characterized in that, The free calcium oxide and free magnesium oxide inside the carbide steel slag are converted into carbonates, and the products include calcium carbonate, magnesium carbonate and nano-sized silica; the calcium carbonate crystal forms include: aragonite, aragonite, calcite and nano-calcium carbonate; the magnesium carbonate crystal forms include: magnesite, trihydrated magnesite, spheroidal magnesite and hydromagnesite. The carbide steel slag exhibits a mixed morphology of multiple mineral phases, with a carbon fixation content of 10-32%. The cementing material is a hydraulic inorganic cementing material, selected from at least one of silicate cement, aluminate cement, sulfoaluminate cement, and solid waste-based cementing materials, preferably solid waste-based cementing materials, with a carbon sequestration content of 2-16% per unit of cementing material; the solid waste-based cementing material is composed of steel slag, blast furnace slag, and desulfurized gypsum in a mass ratio of 2-6:3-7:0.5-2.

9. The application of an auxiliary cementitious material for carbide steel slag, characterized in that, Carbide steel slag auxiliary cementitious material was used to make a paste test block, which was then cured to obtain a hardened body.

10. The application according to claim 9, characterized in that, The curing process specifically involves curing at 20-60℃ under normal pressure for 1-28 days. The hardened body has a 3-day compressive strength of 0.7~8MPa, a 7-day compressive strength of 6~25MPa, and a 28-day compressive strength of 15~60MPa.

Citation Information

Patent Citations

  • Method for fixing carbon dioxide and digesting free calcium oxide in slag micro powder

    CN101851071A

  • Method for mineralizing and fixing carbon dioxide by using strengthened steel slag

    CN103111186B

  • A fluidized bed process and system for directly capturing carbon dioxide from mineralized flue gas

    CN104759203B

  • Technological method for wet decarbonization by using steel slag slurry

    CN108246090A

  • A device for coupled acidification and carbonization modification of steel slag

    CN115626788B